Analisis Laporan Keuangan: Rasio Pasar, Rasio Profitabilitas, Rasio Manajemen Utang: Financial Statement Analysis: Market Ratios, Profitability Ratios, Dept Management Ratios. - Dinda Fauziyah; Tika Anjani; Alfinda Myla; Adiftia Maulana; Renata Putri; Winda Rahmawati (TALI JAGAD JOURNAL, 2026)
This study discusses the analysis of financial statements with a focus on three main types of ratios: market ratios, profitability ratios, and debt management ratios. Market ratios are used to evaluate the valuation of stocks in the capital market relative to the company's financial performance. Profitability ratios measure the company's ability to generate profit from the assets and capital it owns. Debt management ratios assess the proportion of debt in the financing structure and the company's ability to meet its debt obligations. This study is important to provide an overview of management effectiveness, the company's financial health, and to assist investors in making informed investment decisions.